2005
DOI: 10.1158/0008-5472.can-03-3986
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis Inhibition by Vascular Endothelial Growth Factor Receptor-2 Blockade Reduces Stromal Matrix Metalloproteinase Expression, Normalizes Stromal Tissue, and Reverts Epithelial Tumor Phenotype in Surface Heterotransplants

Abstract: Inhibition of vascular endothelial growth factor (VEGF) signaling, a key regulator of tumor angiogenesis, through blockade of VEGF receptor (VEGFR)-2 by the monoclonal antibody DC101 inhibits angiogenesis, tumor growth, and invasion. In a surface xenotransplant assay on nude mice using a high-grade malignant squamous cell carcinoma cell line (A-5RT3), we show that DC101 causes vessel regression and normalization as well as stromal maturation resulting in a reversion to a noninvasive tumor phenotype. Vessel reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(79 citation statements)
references
References 63 publications
6
70
0
3
Order By: Relevance
“…One potential mechanism behind this invasive growth behavior was suggested by analyzing the expression of stromal and tumor-derived MMPs that were previously identified as hallmarks for malignant, invasive HaCaT-ras xenografts. 42,[67][68][69] We found a similar marked induction of stromal MMP-9 and MMP-13 as well as tumor MMP-1 in transplants of mVEGF-164 transfectant and mVEGF-164 plus hPDGF-B mixed transplants. In contrast, stromal MMP-9 was only marginally expressed in benign HaCaT hPDGF-B transfectant transplants, and stromal MMP-13 and tumor-derived MMP-1 were completely lacking.…”
Section: Discussionsupporting
confidence: 64%
“…One potential mechanism behind this invasive growth behavior was suggested by analyzing the expression of stromal and tumor-derived MMPs that were previously identified as hallmarks for malignant, invasive HaCaT-ras xenografts. 42,[67][68][69] We found a similar marked induction of stromal MMP-9 and MMP-13 as well as tumor MMP-1 in transplants of mVEGF-164 transfectant and mVEGF-164 plus hPDGF-B mixed transplants. In contrast, stromal MMP-9 was only marginally expressed in benign HaCaT hPDGF-B transfectant transplants, and stromal MMP-13 and tumor-derived MMP-1 were completely lacking.…”
Section: Discussionsupporting
confidence: 64%
“…invasion (48)(49)(50). As tumor angiogenesis is regulated by the disbalanced activity or expression of angiogenic stimulators and inhibitors (51), our data place G-CSF and GM-CSF among the stimulators of tumor angiogenesis in vivo.…”
Section: Discussionmentioning
confidence: 64%
“…Tumor VEGF, however, stimulated invasion, motility, and gelatinase release by murine and human endothelial cells used as a prototype of VEGF-responsive host cells. Besides endothelial cells, other cells can express MMP9, including pericytes, macrophages, or hematopoietic cells (26). Indeed, immunohistochemical analysis revealed that the cells mostly responsible for the production of host MMP9 in the ovaries of 1A9-VS-1 transplanted mice were inflammatory cells morphologically referable to neutrophils.…”
Section: Discussionmentioning
confidence: 99%